Skema Aktan dan Model Fungsional Novel Sang Keris Karya Panji Sukma Sebagai Bahan Ajar Novel Kelas XII - Nurjanah, Asih; Nurhasanah, Een; Hartati, Dian (Jurnal Ilmiah Wahana Pendidikan, 2024)
The study aims to describe the novel's actant and functional schemes The Kris by Panji Sukma. This research is qualitative research with an analytic descriptive method. The subject of this research is the novel The Krisby Panji Sukma. Meanwhile, the object of this research is an actan and functional scheme. Data collection techniques in this study are reading techniques, note-taking techniques, and library techniques. Data analysis techniques in this study are data reduction, data presentation, and conclusion. The results of the analysis show the potential structure found in the novel Kris Panji Sukma's work totals sixteen schemes which are excerpts from the events in each chapter of the novel. There are ten perfect schemes and six imperfect schemes. Imperfect schemes are dominated by the absence of constraints. The results of the functional model analysis include the entire storyline based on the accounting scheme that has been found. Based on the sixteen functional models disclosed, two incomplete functional models were found. The incompleteness of the model is due to the hanging story. Functional models in novelsSang Dagger Panji Sukma's works are diverse. It is marked by the variety of issues raised in the novel. However, each chapter in the novel has the same common thread, namely talking about keris. The results of this study can be relevant to the teaching materials of literary texts on novel materials. The utilization of research results is expected to be able to add references to Indonesian literary texts that are worthy of being studied by students.